1970
DOI: 10.1017/s0003356100028798
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodism in the ewe: 2. The effects of various patterns of decreasing daylength on the onset of oestrus in clun forest ewes

Abstract: 1970). Photoperiodism in the ewe: 2. The effects of various patterns of decreasing daylength on the onset of oestrus in clun forest ewes. SUMMARYIn six light-proofed buildings experiments were conducted with Clun Forest ewes to determine whether the date of first oestrus was affected by the absolute size of reduction in the case of an abrupt decrease in daylength and by the rate of reduction in the case of a given total decrease in daylength. The mean number of days from the onset of the light treatments to fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 10 publications
3
25
0
Order By: Relevance
“…This is consistent with earlier studies (Ducker et al, 1970;Walton et al, 1977), although a small part of the effect may have been due to the heavier bodyweight of the ewes on short days. There was an unusual degree of synchrony in the onset of oestrus in the ewes kept under natural daylength.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with earlier studies (Ducker et al, 1970;Walton et al, 1977), although a small part of the effect may have been due to the heavier bodyweight of the ewes on short days. There was an unusual degree of synchrony in the onset of oestrus in the ewes kept under natural daylength.…”
Section: Discussionsupporting
confidence: 93%
“…It has long been accepted that the photoperiod is the primary environmental cue controlling seasonal breeding in sheep [11,20,47]. The photoperiodic signal is transduced by the pineal gland into a pattern of melatonin secretion which, in turn, provides a critical endocrine signal to regulate secretion of other hormones involved in the onset and termination of the annual breeding season [4,16].…”
Section: Introductionmentioning
confidence: 99%
“…Yeates (1949) and Hafez (1952) Thwaites and Bowman, 1970). These authors also found that various patterns of increasing daylength affected the onset of anoestrus (Ducker and Bowman, 1970a).…”
Section: Introductionmentioning
confidence: 89%